E-Procurement sebagai Upaya Pencegahan Fraud terhadap Pengadaan Barang dan Jasa di Unit Layanan Pengadaan Provinsi Sumatera Utara - Irine Ika Wardhani; Arifa Pratami; Ikbar Pratama (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
This study aims to analyze the influence of E-procurement, internal control system and religiosity on the prevention of fraud procurement of goods and services in the Procurement Service Unit (ULP) of Goods and Services of North Sumatra Province. This study uses quantifiable method with primary data source obtained in its entirety from the spread of 124 research questionnaires on all employees working in ULP North Sumatra Province. Data analysis in this study using Structural Equation Modelling (SEM) analysis using Partial Least Square (PLS). The results prove that variable e-procerement is proven to have a positive impact on the prevention of fraud procurement of goods and services. Variable relegiusity is proven to have a positive impact on the prevention of fraud procurement of goods and services. Variable internal control system is proven to have a positive impact on the prevention of fraud procurement of goods and services.